AMARANTH FLOUR FROM LOCAL ORIGIN AND GLUTEN-FREE DIET TRENDS (American Journal of Interdisciplinary Research and Development, 2022)
The article provides for the development of a gluten-free diet with the help of amaranth flour of local origin. The problems of availability and cost of gluten-free products are the main ones on the bread market today.